Photodynamic Activity on Biofilm in Endotracheal Tubes of Patients Admitted to an Intensive Care Unit. (20th April 2020) - Soares, Rosane Bassi; Costa, Denis Honorato; Miyakawa, Walter; Delgado, Maria Goretti Temoteo; Garcez, Aguinaldo Silva; Yoshimura, Tania Mateus; Ribeiro, Martha Simões; Nunez, Silvia Cristina
Abstract: Ventilator‐associated pneumonia (VAP) is an infection that arises after endotracheal intubation affecting patients under intensive care. The presence of the endotracheal tube (ETT) is a risk factor since it is colonized by multispecies biofilm. Antimicrobial photodynamic therapy (aPDT) could be a strategy to decontaminate ETTs. We verify if methylene blue (MB) associated with external illumination of the ETT could be an alternative to destroy biofilm. We performed an in vitro and ex vivo study. In vitro study was performed with P. aeruginosa biofilm grew over ETT for 7 days. After treatment, the surviving cells were cultured for 3 days and the biofilm was analyzed by crystal violet absorbance. Ex vivo study employed ETT obtained from extubated patients. aPDT was performed with MB (100 µm ) and red LED (λ = 640±20 nm). We quantified the biofilm thickness and used scanning electron microscopy and fluorescence technique to verify morphological and functional changes after aPDT. Our results showed that bacteria remain susceptible to aPDT after sequential treatments. We also attested that aPDT can reduce biofilm thickness, disrupt biofilm attachment from ETT surface and kill microbial cells. These data suggest that aPDT should be investigated to decrease VAP incidence via ETT decontamination. Abstract : One of the most important etiological factors to the development of ventilator‐associated pneumonia (VAP) is the contamination of the endotracheal tube (ETT). VAP is one of the healthcare‐related infections with high incidence in intensive care units. The biofilm inside the ETT is one of the main causes of the infection, and in our ex vivo study, we demonstrated that antimicrobial photodynamic therapy performed with methylene blue and a red LED was able to detach the biofilm from the ETT wall, diminish the extracellular matrix and kill microbial cells.